An Improved Network Risk Evaluation Metbod Based on Markov Game - Wenfen Liu; Shuwei Zhang; Xin Gong (Dianxin kexue)
Network security risk assessment is an important means of acquiring and mastering the current and future state of network, which is of great significance to maintain the safe operation of the network. An improved risk assessment method based on Markov game that has simply changed the past was presented, in which the risk status of the network assets were classified into fixed categories. Depending on the game relationship between vulnerabilities fixing and threat attacking, this method has more detailed characterization of the network risk. Network attacks and vulnerabilities were sorted, which reduced the state space, making the scale of model input greatly reduced, improving the assessment of large-scale network efficiency. In addition, the relative importance of the hosts was taken into account to distinguish the contribution of different hosts on the network risk. Simulation results demonstrate the feasibility and effectiveness of this method.